Biomechanical loading of instep kick for malaysian footballer - Dayang Khairunnisa, Abang Kiprawi (2012)
Improvements of kicking technique have to be taken care of since good kicking technique is essential for a football player. Therefore, the understanding of biomechanical loading of one of the kicking technique which is instep kick is particularly important for their training process. Biomechanics loading for double instep kick is chosen for this study. However, it is more to comparison of using knee pad or without knee pad while performing one step and two steps of instep kick. The variables from collected data will be analyzed to see the correlation towards the performance between using knee pad or without knee pad in this study. Analysis of data is done by using Silicon Pro Coach Software and statistical analysis is done by using Minitab software and SPSS. Video of subjects while performing double instep kick is analyzed by Silicon Pro Coach software whereas for statistical analysis, linear regression, multilinear regression and correlation analyzed by using Minitab and SPSS software. Through linear regression analysis, velocity and acceleration variable usable in making force equation model and distance is neglected since its having low significant value to force model. The highest velocity can be achieved when performing two step run and without using knee pad which showed 12.6061 m/s. The highest acceleration occur when the subject performing instep kick with two step run and without using knee pad, 630.31 m/s2. Then, the highest value of distance here is when performing instep kick with two step run and without using knee pad which is 48.4611 m and it shows that the biggest hip angle occurred when performing one step run and with the knee pad 140.555° while the biggest knee angle occurred when applying two steps run while using knee pad 153.00 °.